PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP PERILAKU SISWA KELAS XI SMK SEMEN PADANG TAHUN AJARAN 2025/2026 - Oktaviani; Linda Fitria; Popi Radyuli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of social media use on student behavior at Semen Padang Vocational School. This research is a quantitative study using a correlation approach that shows the influence of variable X on variable Y. The number of respondents in the study was 93 people. The sample determination used a total sampling technique where researchers can use samples from the population. Data collection techniques used were questionnaires, observation, and documentation. While the data analysis technique used descriptive analysis and inferential data analysis techniques using simple linear regression analysis. The magnitude of the influence of social media on student behavior at SMK Semen Padang based on the results of the t-test calculation found that social media on student behavior at SMK Semen Padang, this can be proven by the results of a simple regression analysis, namely the results of f count 1.51>1.41 then Ho is rejected and Ha is accepted. So it can be concluded that there is an influence of social media on student behavior at SMK Semen Padang.